Analisis Bauran Pemasaran Jasa Dan Kepercayaan Konsumen Terhadap Pengambilan Keputusan Berwisata Di Masa Adaptasi Kebiasaan Baru Di Kota Makassar - Munawir Nasir; Muhammad Haerdiansyah Syahnur (AkMen JURNAL ILMIAH, 2022)
The purpose of this study is to determine the effect of the marketing mix and trust on tourism industry decision-making during the adaptation period of the Covid 19 in Makassar City. Explanatory Research is a type of social research in which the purpose is to provide a brief definition or explanation of the concepts or patterns studied. A purposive sampling technique was used to select 75 respondents who met the criteria of visitors to tourism locations in Makassar City. The data were gathered via online questionnaires and descriptive data analysis, and the results indicated that it was expected to demonstrate the influence of variables on consumer travel decision-making during the adaptation period of new habits. According to the study's findings, the marketing mix of services and trust has a positive and significant effect on tourists' decision to visit Makassar City during the implementation of the new normal in Makassar.